Mutation analysis of the AATF gene in breast cancer families - Haanpää, Maria (BioMed Central, 2009)
BACKGROUND: About 5-10% of breast cancer is due to inherited disease predisposition. Many previously identified susceptibility factors are involved in the maintenance of genomic integrity. AATF plays an important role in the regulation of gene transcription and cell proliferation. It induces apoptosis by associating with p53. The checkpoint kinases ATM/ATR and CHEK2 interact with and phosphorylate AATF, enhancing its accumulation and stability. Based on its biological function, and direct interaction with several known breast cancer risk factors, AATF is a good candidate gene for being involved in heritable cancer susceptibility. METHODS: Here we have screened the entire coding region of AATF in affected index cases from 121 Finnish cancer families for germline defects, using conformation sensitive gel electrophoresis and direct sequencing. RESULTS: Altogether seven different sequence changes were observed, one missense variant and six intronic ones. Based on the in silico analyses of these sequence alterations, as well as their occurrence in cases and controls, none of them, however, were predicted to be pathogenic. CONCLUSIONS: To our knowledge, this is the first study reporting the mutation screening of the AATF gene in familial breast cancer cases. No evidence for the association with breast cancer was observed.